Development of drive cycle and assessment of the performance of auto-LPG powered public utility jeepneys in Makati city, Philippines Nirman Pokharel. - Pokharel, Nirman (2013)
The drive cycle for the Auto-LPG Jeepney is developed. Five statistical candidate drive cycles are initially selected which had the least absolute value differences. One drive cycle is finally selected and is found to be non-drivable due to aggressive acceleration in some parts; thus, it had to undergo smoothening using Moving Averages Method. The final smoothened drive cycle has the following properties: maximum speed 43.2 km/h; average speed 7.7 km/h; maximum acceleration of 0.9 m/s²; duration of 1,279 seconds; and, idle time share of 44.6%. The developed drive cycle is tested on the chassis dynamometer of the U.P. Vehicle Research and Testing Laboratory to determine its drivability and maximum power. The average maximum power is measured at 51.8 kW. An on-road test of three (3) Auto-LPG jeepney units plying the PRC-Mantrade route in Makati City is conducted where passenger occupancy, travel distance and fuel consumption (full tank method) are generated. The fuel efficiency is estimated at 3.54 km/li or 8.55 Pesos/km operational cost. Daily average revenue of Auto-LPG Jeepney driver was 2,874 Pesos based on on-road tests in weekdays and 3,167 Pesos from the interviews. Deducting the total reported expenses, the average take home pay or net income of Auto-LPG drivers was 1,039 per day. The average daily revenue of diesel-jeepney drivers was 2,470 and average daily home pay or their net income was 434 Pesos per day as reported.
Thesis (M.S. Civil Engineering)--University of the Philippines, Diliman.
Keywords: Liquified petroleum gas; Jeep automobile